Pengarusutamaan Pendidikan Gender Dalam Lingkup Pendidikan Agama Islam - Safitri, Ayu; Awalia, Rubi (ILJ: Islamic Learning Journal, 2025)
This journal discusses the mainstreaming of gender education in the scope of Islamic Religious Education (PAI) as an effort to achieve gender equality and justice in society. Gender injustice is still an important issue that includes discrimination, subordination, and stereotypes that hinder equal access and opportunities for men and women. Education plays a strategic role in shaping the character and mindset of individuals, as well as fostering gender awareness from an early age. Through the integration of gender perspectives in the PAI curriculum, it is expected to eliminate gender bias and create an inclusive educational environment. The research method used is a literature study with a descriptive approach, collecting data from various relevant sources. The results show that although there are opportunities for gender equality in Islamic education, challenges such as stereotypes, cultural constraints, and economic factors still need to be overcome. The journal suggests the need for collaboration between educators, educational institutions and society to effectively implement gender justice values in education, so as to produce a gender-aware generation that contributes to society.